Biology of bryozoans - Woollacott, Robert M.; Zimmer, Russel L. (Academic Press, 1977)
Biology of Bryozoans covers some of the unusual and even unique systems and aspects of bryozoans. The book discusses the gametogenesis of bryozoans; the brooding patterns of bryozoans; and the structure and classification of gymnolaemate larvae. The text also describes the metamorphosis, ancestrulae, and coloniality in bryozoan life cycles; the ultrastructure, mineralogy, and development of bryozoan skeletons; and polymorphism in marine bryozoans. Bryozoan feeding and culture; experimental techniques and culture methods; and the problem of the funiculi and the communications are also considere.